Applications of rice husk ash as green and sustainable biomass - Moayedi, Hossein; Aghel, Babak; Abdullahi, Mu'azu Mohammed; Nguyen, Hoang; Safuan A Rashid, Ahmad (Journal of cleaner production, 2019)
Research on agricultural wastes management, as a natural resource material, is state of the art and desirable subject in many engineering subcategories. The benefits include ease of access and implementation, affordability and environmental friendliness. Optimal use of agricultural wastes has always been a concern for humans, and the utilization of them for various purposes is an efficient way of environmental management. Among bio-waste ashes, some of them such as rice husk ash has a high pozzolanic content that stems from their abundant silica concentration. The significantly low reaction time and the high utilization of these materials, when compared to traditional mechanical methods, has generated interest from researchers. The present paper surveys the experimental studies of biomass waste ash as a pozzolanic additive for engineering applications. This paper initially provides some essential background information includes agricultural waste ash preparation procedures and its composition, then reviews the various physical and chemical pretreatment methods. Finally, the paper explores the potential application of rice husk ash as green and sustainable material in various industries. •The Rice husk is an agricultural residue can use as natural resources.•The use of RHA contributes to economic and environmental benefits.•RHA can potentially stabilize the soil and reduce construction cost.•RHA as a raw material can use as adsorbent or catalyst for biodiesel production.